Quasi-Distributed Fiber Bragg Grating Sensing Using Stepped Incoherent Optical Frequency Domain Reflectometry - Werzinger, Stefan; Bergdolt, Sven; Engelbrecht, Rainer; Thiel, Torsten; Schmauß, Bernhard (Journal of Lightwave Technology, 2016)
We examine the quasi-distributed interrogation of fiber Bragg grating arrays (FBGA) with the method of stepped incoherent optical frequency domain reflectometry (IOFDR) combined with wavelength scanning of a tunable laser source. The technique of IOFDR provides some advantages over traditional time division multiplexing schemes, because continuous wave modulation of the light intensity instead of short and low energy pulses is used, maximizing the reflected signal received from the sensor fiber. Moreover, an electrical heterodyne demodulation by a microwave vector network analyzer provides a low-noise detection, while achieving high spatial resolutions down to the centimeter range. A quasi-distributed temperature measurement with ten FBGs of 0.5% reflectivity is demonstrated. In the experiment, a root mean square temperature error of 0.3 K and a maximum error of 1 K is observed, using a fiber-coupled power of only -12 dBm. A spatial two-point resolution of 2.14 cm is achieved, which enabled a successful interrogation of FBGAs with 20 and 30 cm spacings. The potential multiplexing capability of the given setup could reach more than 50 gratings in a 30 cm spacing at a measurement rate of 50 s/n
lhft_intern.bib::Werzinger2016c